Biological reproducibility of circulating P-Selectin, Thrombopoietin, GPIIb/IIIa and Thrombomodulin over one year - Graf, Mirja E.; Sookthai, Disorn; Johnson, Theron S.; Schübel, Ruth; Katzke, Verena; Bugert, Peter; Hoffmeister, Michael; Kaaks, Rudolf; Kühn, Tilman (Clinical biochemistry, 2017)
Background: Enhanced platelet activation has been implicated in several pathophysiological processes. Here, we evaluated the biological reproducibility of circulating P-Selectin, Thrombomodulin (TM), Thrombopoietin (TPO), and Glycoprotein IIb/IIIa (GPIIb/IIIa) to assess whether these analytes can be used as reliable biomarkers of platelet activation in epidemiological studies. Methods: We measured circulating P-Selectin, TM, TPO and GPIIb/IIIa by immunoassays in two blood samples of 78 participants of the EPIC Heidelberg study (47-80years, 50% female) that were collected one year apart. Biological reproducibility of biomarker levels over time and associations with routine biochemistry parameters were assessed by Spearman's correlation coefficients. Results: Statistical analyses revealed good reproducibility over one year for two of the analyzed markers, with Spearman coefficients of ρ=0.80 (P-Selectin) and ρ=0.73 (TPO) and reasonable reproducibility for TM (ρ=0.63) and GPIIb/IIIa (ρ=0.51). Levels of P-Selectin, TM, TPO and GPIIb/IIIa were not significantly associated with routine biochemistry parameters, such as glucose, HbA1c, LDL, HDL, Triglycerides and CRP. Conclusions: Our findings suggest that a single assessment of P-Selectin, TM, TPO and GPIIb/IIIa at baseline in prospective epidemiological studies is appropriate to investigate associations between platelet activation and risks of chronic diseases.
Gesehen am 19.06.2018
Available online 29 May 2017